Present-day physiotherapy in the prevention and treatment of complications after abortion in the I trimester - M V Ipatova; T B Malanova; Yu V Kubitskaya (IP Berlin A.V., 2015)
The article presents the indications, contraindications, specific techniques for using various physical factors in various, individually controlled and differentiated ways, in patients after abortion up to 12 weeks by different methods. Physical factors are used at all in order to prevent possible complications, as well as for the treatment of already established complications in women with a history of somatic and gynecological diseases in combination with drug therapy. Displaying differential use of medical factors, depending on the age of patients, parity, type of abortion, individual response to physiotherapy.